Analisis Psychology Capital dan Kinerja Pegawai Puskesmas Rasana’e Timur Kota Bima - Nurhidayati, Restu; Damayanti, Nyoman Anita; Ramadhani, Aulia (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The research to describe psychological capital and employee performance in east Puskemas Rasana’e. The focus of this study is on psychological capital and employee performance. The method of this research is descriptive. Populations in this research are PNS 49 employees. The sampling used in this research is total sampling. Data on this research was collected by a questioner and shared with all employees, as many as 49 respondents. The result is that employees had good psychological capital with a score of 4.70. This above-value average has a minimum of 1 maximal 6. And employee performance had a good score of 3.30. This above-value average has a minimum of 1 maximal 5. Psychology capital has four dimensions: (self-efficacy, hope, resilience, and optimism). Each dimension has a contribution to every person's ability to do the job optimally. Employee performance means the employee is capable of a good task.